IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN MANGGARAI BARAT - Fransiska Heldiana Juita (Akuntansi Prima, 2024)
This research aims to find out the implementation of parking retribution policy in an effort to increase local revenue of West Manggarai Regency by using George Edwar III's theory as the main requirement for the success of the implementation process, namely: communication, disposition, bureaucratic structure and resources (Edward III in Ningsih, 2020). The data analysis method used in this research is descriptive qualitative research using data collection techniques in the form of interviews, observations and documentation studies. The results showed that: 1) Communication carried out by the transportation department has been running quite well by providing information about policies to parking attendants and conducting socialization to the community. 2) Resource factors such as human resources that are quite good in quantity and quality, adequate budget resources and adequate infrastructure resources even though their utilization has not been maximized. 3) Disposition/attitude of policy implementers has been carried out quite well according to their duties/functions, although in the field several obstacles were found such as parking attendants who did not provide tickets and the attitude of people who were less concerned about the importance of tickets as proof of payment of legal parking fees. 4) Implementation of the bureaucratic structure has been quite well implemented by following the applicable regulations and existing mechanisms. The supervision and evaluation carried out by the West Manggarai Transportation Agency on a regular basis. Keywords: Local Revenue, Public Policy Implementation, Parking Retribution